2015
DOI: 10.33585/cmy.67203
|View full text |Cite
|
Sign up to set email alerts
|

Contributions to the Finnish aphyllophoroid funga (Basidiomycota): new and rare species.

Abstract: This article contributes to the knowledge of Finnish aphyllophoroid funga (mainly polypores and corticioids) with nationally or regionally new species and records of rare species. The record of Tubulicrinopsis cystidiata is the second in the world and Tomentella fuscocinerea

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(10 citation statements)
references
References 9 publications
0
10
0
Order By: Relevance
“…This is the ninth record in Finland. Previous records derive throughout Finland (Kotiranta et al 2009, Kunttu et al 2015. Species is found mainly on large trunks of Pinus sylvestris.…”
Section: Phanerochaete Livescens (P Karst) Volobuev and Spirinmentioning
confidence: 96%
See 2 more Smart Citations
“…This is the ninth record in Finland. Previous records derive throughout Finland (Kotiranta et al 2009, Kunttu et al 2015. Species is found mainly on large trunks of Pinus sylvestris.…”
Section: Phanerochaete Livescens (P Karst) Volobuev and Spirinmentioning
confidence: 96%
“…This is the eigth locality in Finland. Previous localities are in Tervola (3c), Rovaniemi (3c), Pudasjärvi (4a), Taivalkoski (4a), and Kemijärvi (4b), Rovaniemi (4b) (Kotiranta et al 2009, Kunttu et al 2015. The number of occupied trunks is much higher.…”
Section: Phanerochaete Livescens (P Karst) Volobuev and Spirinmentioning
confidence: 98%
See 1 more Smart Citation
“…27 New to Middle Boreal, Northern Carelia -Kainuu (3b). This is the fourth record of the species in Finland; previous records were from Helsinki (1b), Luhanka (2b), and Utsjoki (4d) [2,28].…”
Section: Tulasnella Thelephorea 6thmentioning
confidence: 99%
“…There are many studies on species diversity and taxonomy of Tomentella reported in Europe, while systematic collection, genetic diversity researches and classification of this species is still scarce in Finland at present, and approximately 23 species were recorded (Kotiranta et al 2009;Kunttu et al 2012;Kunttu et al 2015;Kuhar et al 2016). However, three species, T. crinalis (Fr.)…”
Section: Introductionmentioning
confidence: 99%